Insulin resistance is associated with reduced capillary permeability of thigh muscles in patients with type 2 diabetes - Mooshage, Christoph; Tsilingiris, Dimitrios; Schimpfle, Lukas; Kender, Zoltán; Aziz-Safaie, Taraneh; Hohmann, Anja; Szendrödi, Julia; Nawroth, Peter Paul; Sturm, Volker Jörg Friedrich; Heiland, Sabine; Bendszus, Martin; Kopf, Stefan; et al. (The journal of clinical endocrinology & metabolism, 2024)
Insulin-mediated microvascular permeability and blood flow of skeletal muscle appears to be altered in the condition of insulin resistance. Previous studies on this effect used invasive procedures in humans or animals.The aim of this study was to demonstrate the feasibility of a noninvasive assessment of human muscle microcirculation via dynamic contrast-enhanced (DCE)-magnetic resonance imaging (MRI) of skeletal muscle in patients with type 2 diabetes (T2D).A total of 56 participants (46 with T2D, 10 healthy controls [HC]) underwent DCE-MRI of the right thigh at 3 Tesla. The constant of the musculature's microvascular permeability (Ktrans), extravascular extracellular volume fraction (ve), and plasma volume fraction (vp) were calculated.In T2D patients, skeletal muscle Ktrans was lower (HC 0.0677 ± 0.002 min−1, T2D 0.0664 ± 0.002 min−1; P = 0.042) while the homeostasis model assessment (HOMA) index was higher in patients with T2D compared to HC (HC 2.72 ± 2.2, T2D 6.11 ± 6.2; P = .011). In T2D, Ktrans correlated negatively with insulin (r = −0.39, P = .018) and HOMA index (r = −0.38, P = .020).The results signify that skeletal muscle DCE-MRI can be employed as a noninvasive technique for the assessment of muscle microcirculation in T2D. Our findings suggest that microvascular permeability of skeletal muscle is lowered in patients with T2D and that a decrease in microvascular permeability is associated with insulin resistance. These results are of interest with regard to the impact of muscle perfusion on diabetic complications such as diabetic sarcopenia.